MECHANISMS FOR THE EFFECTIVE ORGANIZATION OF THE COMMUNICATION PROCESS - Mamadaliyeva Lola Abduvahobovna (Western European Studies, 2023)
This article reflects on the role of human behavior in communication and its organization, the thinking of the individual, the ability to analyze and evaluate the universe and its image, is formed in the process of communication, through communication, a person acquires social experience and culture.
Keywords: Communication; personality; behavior